Use of Mobile Applications for Foreign Language Lexical Competence Formation - Horbatiuk, Larysa; Kravchenko, Nataliia; Alieksieieva, Hanna; Lipych, Victoriia; Rozumna, Tetyana (Journal of History Culture and Art Research, 2019)
The article deals with the problem of foreign language lexical competence formation of non-philological specialties students, which is the basis for foreign-language communicative competence and a compulsory component of a future specialist’s training. The relevance of using mobile technologies in the process of teaching students a foreign language to increase the qualitative level of lexical competence is substantiated. The analysis of mobile applications for the study of a foreign language has shown that there is no unambiguous approach to their development and implementation, focused on the specifics of future students’ professional activities. As a result of the study, the structure, functionality, and design of a mobile application for the study of English by students of non-philological specialties were developed. A mobile application for developing the English language lexical competence for the Android operating system with the help of the integrated Android Studio mobile application development environment has been developed. Experimental testing of the effectiveness of applications in foreign language classes for mobile applications focused on the specifics of students’ future professional activities has shown the positive impact of specialized mobile applications on the level of students' knowledge of the foreign language vocabulary.